Understanding COVID-19 in Disaster Perspective Based on the Tatsunami Manuscript Kyai Haji Maimun Zubair - Fathimatuz Zahra Anis (UIN Sunan Kalijaga Yogyakarta, 2021)
Coronavirus 19 is a pandemic that has affected many parts of life, including religion. There are many viewpoints about the COVID-19 disaster in Islam. The Tatsunami Manuscript by KH. Maimun Zubair is one of the manuscripts that discusses disasters. This manuscript is the most recent Indonesian literature about disaster that can be used to comprehend the COVID-19. This study using the hermeneutic methods to reveal the meaning of the COVID-19 based on the manuscript's perspective and its significance for religious life. The results of the study show that this manuscript does not only contain the concept of disaster, but also offers mitigations and solutions that can be applied in the case of COVID 19.